PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG DI TAMAN BERMAIN BANTO ROYO PADA MASA PASCA NEW NORMAL - Raftul Fedri; Dewi Anggraini (Ensiklopedia of Journal, 2022)
This research is a type ofaquantitative associative research using questionnaires and the research population is Banto Royo Playground visitors, with a sample of 100 respondents and the sampling technique is accidental sampling. Data analysis used multiple regression analysis. Based on the results ofaresearch and discussion, the regression equation  Y = 2,607 + 0.252X1 + 0.294X2 + 0,306X3 + 0,473X4 + 0,269X5 + e is obtained. So it can be concluded that there is a simultaneous and partial effect ofiservice quality on visitor satisfaction at Banto Royo Playground during  the new normal period. That is, the higher the quality ofaservice provided by the Banto Royo Playground, the higher the level ofsvisitor satisfaction. Then it is known that the value of Adjusted R2 is 0.759, where the variables of responsiveness, assurance, physical evidence, empathy and reliability contribute to the influence of the visitor satisfaction variable by 75.9%, the remaining 24.1% is influenced by other variables outside of this  study.  Based on the conclusions  of the study, it is recommended that the Banto Royo Playground will further improve and adjust the quality of its services in accordance with the Covid-19 health protocol.Keywords: Service Quality, Banto Royo Tourism Object, Factors